Naming my reality: a youth narrative on drug abuse and gangsterism in the Cape Flats - Chetty, Rajendra (Acta criminologica, 2017)
This article provides a youth narrative on drug abuse and gangsterism in the Cape Flats suburb of Mitchell’s Plain. The narrative engages with the experiences within a single street, Shepherd Way, in one of the highest crime areas in South Africa. The account attempts to bring temporal order to what would otherwise be experienced as a series of chaotic events, given the social complexity characteristics of gangsterism and drug abuse. Narratives often run counter to expectations, making the familiar unfamiliar, and seldom does a story have a single reading or meaning. This study provided an opportunity for the researcher to engage with young persons’ lived experiences by committing to holding conversations with them using their concerns as a starting point. In this case, the focus issue being drug abuse and how it influences their quality of life. The primary purpose then of the article was to engage with the ways in which youth name their reality in high crime areas concomitant with foregrounding the voice of the youth via research into their lives. Hence, this narrative is also a commitment to valuing and attending to the here-and-now of young people’s experiences rather than just focusing on the researcher’s agenda of collecting data on drug abuse and crime. The theoretical underpinnings for the article are Bleakley’s (2005) notion of narrative inquiry and Solorzano and Yosso’s (2002) conception of counter-storytelling. The key finding emanating from this study being that the exposure of youth to anti-social learning in gang and drug subcultures, and the vacuity of economic opportunity in high poverty areas provide the ideal environment for drug abuse and violent gangs. The article demonstrates the importance of conversation and open dialogue embedded in an appreciation of the socio-economic context of vulnerable youth.